Implementation of Diarium as a Digital Internal Communication Medium at PT Nutech Integrasi - Mayva Eka Wulandary; Ika Sartika; Renny Soelistiyowati (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
The development of digital technology has driven the transformation of communication in the workplace, including at PT Nutech Integrasi, which is part of TelkomGroup. This study aims to analyze the implementation of the Diarium application as a digital internal communication medium using the SMCR communication model and the Uses and Gratifications Theory (UGT). This study uses a qualitative descriptive approach with data collection techniques such as interviews, observation, and documentation. The results show that the implementation of Diarium reflects the SMCR model as a whole, starting from the process of sending, delivering, and receiving messages among employees. Diarium also fulfills the four main categories of needs in UGT: the need for information, personal identity, social integration, and entertainment. This application not only functions as a channel for disseminating information, but also creates a digital space for interaction and collaboration among employees. Thus, Diarium plays a strategic role in strengthening transparent, efficient, and adaptive internal communication in the era of digital transformation.